Hospital Charge and Health-Care Quality in Bariatric Surgery. Issue 2 (February 2017) - Telem, Dana A.; Yang, Jie; Altieri, Maria; Talamini, Mark; Zhang, Qiao; Pryor, Aurora D.
To determine if hospital charges correlate with patient outcomes after bariatric surgery. A retrospective review of 46, 180 patients who underwent bariatric surgery from 2004-2010 was performed. Patients were identified using the New York Statewide Planning and Research Cooperative System database. Hospitals were categorized on estimates from a multiple linear regression model for charge: low (<$25, 027.00), medium ($25, 027.00–$35, 449.00), and high (≥$35, 449.01). Patient outcomes were compared among the charge classification. Of the 46, 180 patients, 24 per cent underwent operations in low-, 26 per cent in medium-, and 23, 082 (50%) in high-charge hospitals. Controlling for patient demographics, comorbidity, insurance, and operative procedure, multivariable logistic regression demonstrated no significant difference in major complication or mortality among charges. Hospital charge does not correlate with improved outcomes. This is significant given the adverse association between price inflation and rising insurance premiums. Inflated hospital charges may also discriminate against certain patient populations including the uninsured and those with high-deductible insurance plans.